Tackling Single-Use-Plastic in small touristic islands to reduce marine litter: co-identifying the best mix of policy interventions - Guittard, Alice; Akinsete, Ebun; Demian, Elias; Koundouri, Phoebe; Papadaki, Lydia; Tombrou, Xenia (Frontiers in Environmental Economics, 2023)
Marine litter is a global issue of increasing environmental and economic concern, with Single-Use-Plastic (SUP) pollution being a leading challenge. The tourism industry has been identified as one of the major contributors to marine plastic pollution and required to take urgent actions. Small islands are particularly vulnerable and need locally adapted strategies to effectively tackle this issue. This study proposes the use of a participatory system-based approach to co-design, with local stakeholders, a roadmap tackling Single-Use-Plastic (SUP) in the hospitality industry of small touristic islands. The methodology was implemented on small Greek islands in the Mediterranean Sea, where lack of knowledge and awareness, limited financial resources and expertise, and low efficiency of the waste management systems were identified as the main challenges. Representatives from policy, industry, civil society and academia were involved in a participatory co-creation process to co-identify the best mix of policy instruments and innovations (social and technological) adapted to the local island context, capable of reducing plastic consumption and littering in the island; while fostering behavioural change (from the perspectives of both consumers and local businesses). A roadmap of actions was co-developed as the basis of the municipal ‘Island Free-SUP strategy’. The roadmap was based on the principles of a Circular Economy, responsible consumption (reduce, re-use, recycle), raising awareness, positive economic incentives, capacity building and partnership within the quadruple helix (academia, business, public authorities and civil society). The study provides 1) an innovative participatory methodology to tackle SUP issues replicable in various contexts, 2) evidence on key barriers to be overcome by the local tourism industry in small island communities in order to phase out the use of SUPs.